Structure Of Mangrove Community In Palaes Village Coastal West Likupang District, North Minahasa - Tulenan, Maryand M.; Wantasen, Adnan S.; Rembet, Unstain N. W. J. (Jurnal Ilmiah PLATAX, 2018)
Indonesia is a tropical archipelago shaped (13,664 Island) with an estimated coastline along (95,181 km) get hold of a good area for the growth of mangrove plants. ). The area thrives in mangrove estuaries or estuaries which is the ultimate goal of the organic particles or sediment mud washed from upstream akibar the presence of erosion. The fertility of the region is also determined by the presence of the nutrient mentransportasi of ups and downs. According to the Directorate General of Rehabilitas Social Forestry land and extensive Mangrove Forests in Indonesia in 1999 was estimated at 8.60 million hectares will be but around 5.30 million hectares in a State of disrepair. While FAO data (2007) extensive Mangrove Forests in Indonesia in 2005 only reaches 3,062,300 haor 19% of the vast Mangrove Forests in the world and the largest in the world surpassing Australia (10%) and Brazil (7%). Mangrove forest condition in the village of Palaes still good enough, this is because the villagers very Palaes keep the existence of mangrove forests. Additionally the utilization of mangrove forests for household needs Palaes's village community is relatively small and yet still giving effect to the environment of mangrove ecosystems. This funded research activities in the area of the coastal village of Palaes Sub-districtLikupang Barat Regency North Minahasa in North Sulawesi province, in may 2016. Use the quadrant method followed by the analysis of the community structure. Quadrant method undertaken by the way pull line transek daro land into the ocean then put the quadrant line 10. After quadrant is laid do data retrieval of vegetation after it conducted an analysis of the data by using the structure of the community. Based on the types of mangroves found in the village of Palaes Sub-district Likupang Barat Regency North Minahasa mangrove species found 6 different family and Rizhopora apiculata is a species of the most influential in the mangrove community in the area of such. And found the value of diversity index 1.73. The identification of the types of mangroves found in the village of Palaes Sub-district Likupang Barat Regency North Minahasa found as many as 501 individuals from 6 species in 4 families namely Rizophoraceae, Lytraceae, Meliaceae and Avicenniaceae as for species found namely Rizhopora mucronata, Sonneratia caseolaris, Rizhopora apiculata and Bruguiera gymnorrhiza, Xylocarpus granatum,and Avicennia officinalis.Keys: Mangrove, environment, vegetation, komonitas. AbstrakIndonesia merupakan daerah tropis berbentuk kepulauan (13.664 pulau) dengan garis pantai yang diperkirakan sepanjang (95.181 km) meenjadi kawasan yang baik bagi pertumbuhan tanaman mangrove. ). Mangrove tumbuh subur di daerah muara sungai atau estuari yang merupakan daerah tujuan akhir dari partikel-partikel organik ataupun endapan lumpur yang terbawa dari daerah hulu akibar adanya erosi. Kesuburan daerah ini juga ditentukan oleh adanya pasang surut yang mentransportasi nutrient.Berdasarkan data Direktorat Jendral Rehabilitas Lahan dan Perhutanan Sosial luas hutan Mangrove di Indonesia pada tahun 1999 diperkirakan mencapai 8.60 juta hektar akan tetapi sekitar 5.30 juta hektar dalam keadaan rusak. Sedangkan data FAO (2007) luas hutan Mangrove di Indonesia pada tahun 2005 hanya mencapai 3,062,300 ha atau 19% dari luas hutan Mangrove di dunia dan yang terbesar di dunia melebihi Australia (10%) dan Brazil (7%).Kondisi hutan mangrove di Desa Palaes masih cukup baik, hal ini dikarenakan masyarakat Desa Palaes sangat menjaga keberadaan hutan mangrove. Selain itu pemanfaatan hutan mangrove untuk kebutuhan rumah tangga masyarakat Desa Palaes relatif masih kecil dan belum menimbulkan dampak terhadap lingkungan ekosistem mangrove.Kegiatan Penelitian ini di laksanakan di kawasan pesisir pantai Desa Palaes Kecamatan Likupang Barat Kabupaten Minahasa Utara Provinsi Sulawesi Utara, pada bulan Mei 2016. Menggunakan metode kuadran yang dilanjutkan dengan analisis struktur komunitas.Metode kuadran dilakukan dengan cara menarik line transek daro darat ke laut kemudian meletakkan sebanyak 10 line kuadran tersebut. Setelah kuadran diletakkan dilakukan pengambilan data vegetasi setelah itu dilakukan analisis data dengan menggunakan struktur komunitas.Berdasarkan jenis mangrove  yang ditemukan di Desa Palaes Kecamatan Likupang Barat Kabupaten Minahasa Utara ditemukan  6 spesies mangrove dari famili yang berbeda dan Rizhopora apiculata  merupakan spesies yang paling berperan dalam komunitas mangrove di daerah tersebut. Dan didapati nilai indeks keanekaragaman 1,73.Identifikasi jenis mangrove yang ditemukan di Desa Palaes Kecamatan Likupang Barat Kabupaten Minahasa Utara ditemukan sebanyak 501 individu dari 6 spesies yang termasuk dalam 4 famili yaitu Rizophoraceae, Lytraceae, Meliaceae dan Avicenniaceae Adapun spesies yang ditemukan yaitu  Rizhopora mucronata, Rizhopora apiculata, Sonneratia caseolaris dan Xylocarpus granatum, Bruguiera gymnorrhiza,dan Avicennia officinalisKeys : Mangrove,Lingkungan, Vegetasi, komonitas.